Intercultural Competence in ELT: Does It Really Matter for English Teachers in Indonesia? - Ahmad Sugianto (Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
Due to globalisation, having an effective communicative skill becomes a pivotal issue. To make effective communication, not only do people require adequate language skills but also the intercultural competence through which mutual understanding across the cultural boundary can be attained should be taken into account. Thereby, English teachers duties are expected not only to provide and facilitate students to gain English skills but also intercultural competence. This study aimed to reveal the EFL teachers' views and beliefs regarding intercultural competence in English teaching practice. The subjects comprised twenty-nine teachers having experience in teaching at some educational institutions, namely schools, universities, and English courses. Based on the collected data using questionnaires and interviews, it was found that most of the teachers had positive views of integrating cultures and intercultural competence into their English teaching practice. Besides, they viewed cultures as an inseparable part of the language. Moreover, teachers' knowledge of the target culture was found to be categorized high. In their teaching practice, they reported that various techniques were utilized to facilitate intercultural language teaching. However, it was found that the way the target cultures were integrated into English teaching had not been adequately considered good; hence, some systematic endeavor was suggested to cope with the issue.